2019
DOI: 10.1111/irv.12669
|View full text |Cite
|
Sign up to set email alerts
|

Use of lentiviral pseudotypes as an alternative to reassortant or Triton X‐100‐treated wild‐type Influenza viruses in the neuraminidase inhibition enzyme‐linked lectin assay

Abstract: Background Formulation of neuraminidase (NA) within influenza vaccines is gaining importance in light of recent human studies. The enzyme‐linked lectin assay (ELLA) is considered a reliable assay to evaluate human anti‐NA antibodies. Objectives To overcome interference by hemagglutinin (HA)‐specific antibodies and detect neuraminidase inhibitory (NI) antibodies only, two different sources of antigen have been studied in ELLA: reassortant viruses with a mismatched avian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…All values were normalized against the highest PV value obtained (100% OD 450 ) and the sample diluent only control (0% OD 450 ). Traditionally, 90% activity is optimal for use in the inhibition assay (33,39), however, we also set the additional criteria of the OD 450 to be a minimum of 2.0 for use in pELLA inhibition. All human and avian PV produced demonstrated NA enzymatic activity and met the additional criteria we set for use in pELLA inhibition ( Figure 2C ) apart from bat N10 and N11.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All values were normalized against the highest PV value obtained (100% OD 450 ) and the sample diluent only control (0% OD 450 ). Traditionally, 90% activity is optimal for use in the inhibition assay (33,39), however, we also set the additional criteria of the OD 450 to be a minimum of 2.0 for use in pELLA inhibition. All human and avian PV produced demonstrated NA enzymatic activity and met the additional criteria we set for use in pELLA inhibition ( Figure 2C ) apart from bat N10 and N11.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, pseudotype virus (PV) can also be used as a substitute to wild type virus in these assays. Neuraminidase pseudotyped viruses have already been successfully used in place of reassortant virus or Triton X-treated wild type virus in the ELLA assay for N1 and N2 subtypes (38,39) As NA has the potential to be included in a more broadly protective vaccine approach, a toolbox of assays capable of assessing NA inhibition will be required. To this end, we have produced an NA PV library encompassing IAV N1-N11 and IBV from the Victoria-like (B/Vic) and Yamagata-like (B/Yam) lineages for use in the pELLA assay and potentially the NA-Fluor™ assay.…”
Section: Introductionmentioning
confidence: 99%
“…The enzymatic activity of recombinant NA proteins was determined by the cleavage of two specific substrates of NA, 2′-(4-methylumbelliferyl)-α-D-N-acetylneuraminic acid (MUNANA) ( Job et al, 2018 ; Ju et al, 2018 ) and fetuin ( Prevato et al, 2015 ; Biuso et al, 2019 ) as previously described, with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Although the MN assay is commonly used in the evaluation of influenza virus vaccines, it has demonstrated significant inter-laboratory variability [ 95 ], in addition to the risk of working with highly pathogenic strains; as such, studies have shown pseudotyped LV neutralisation assays as a reliable alternative [ 96 ]. Further, a pseudotyped LV has been used as an alternative source of antigen for enzyme-linked lectin assays (ELLA), measuring antibodies raised to neuraminidase and alleviating complications of working with reassortant or detergent-treated viruses [ 97 , 98 ].…”
Section: Applications In Serological Studiesmentioning
confidence: 99%